2017
DOI: 10.1016/j.gca.2016.11.038
|View full text |Cite
|
Sign up to set email alerts
|

The accretion and impact history of the ordinary chondrite parent bodies

Abstract: A working timeline for the history of ordinary chondrites includes chondrule formation as early as 0-2 Ma after our Solar System's earliest forming solids (CAIs), followed by rapid accretion into undifferentiated planetesimals that were heated internally by 26 Al decay and cooled over a period of tens of millions of years. There remains conflict, however, between metallographic cooling rate (Ni-metal) and radioisotopic thermochronometric data over the sizes and lifetimes of the chondrite parent bodies, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
87
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(94 citation statements)
references
References 63 publications
7
87
0
Order By: Relevance
“…Blackburn et al. () further suggested that the ages of Ca‐phosphates show a younging trend from ~4560 Ma (type 4) to 4500 Ma (type 6) with increasing petrologic type, which supports the onion‐skin model (e.g., Trieloff et al. ).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Blackburn et al. () further suggested that the ages of Ca‐phosphates show a younging trend from ~4560 Ma (type 4) to 4500 Ma (type 6) with increasing petrologic type, which supports the onion‐skin model (e.g., Trieloff et al. ).…”
Section: Discussionmentioning
confidence: 76%
“…Several Ca-phosphates from unshocked ordinary chondrites have yielded Pb-Pb ages clustering between 4.50 and 4.56 Ga, recording the timing of cooling below the Ca-phosphate closure temperature (i.e.,~500°C) (G€ opel et al 1994;Amelin 2000;Bouvier et al 2007). Blackburn et al (2017) further suggested that the ages of Ca-phosphates show a younging trend from 4560 Ma (type 4) to 4500 Ma (type 6) with increasing petrologic type, which supports the onion-skin model (e.g., Trieloff et al 2003). Thus, ordinary chondrite parent bodies experienced a short period of heating exceeding Ca-phosphate closure temperature for <60 Myr after their formation (G€ opel et al 1994;Bennett and McSween 1996;Trieloff et al 2003).…”
Section: Multiple Shock Heating Eventsmentioning
confidence: 72%
“…; Sugiura and Fujiya ; Blackburn et al. ). As such, our upper accretion age of 1.8 ± 0.2 Myr derived from the 54 Cr signature using the same initial 26 Al/ 27 Al value is in excellent agreement with the accretion age based on thermal modeling.…”
Section: Discussionmentioning
confidence: 99%
“…; Blackburn et al. ). As such, μ 54 Cr signatures of H chondrites are consistent with rapid accretion via turbulent accretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation